The Effect of Autologous Platelet Lysate Eye Drops: An In Vivo Confocal Microscopy Study. (20th April 2016) - Fea, Antonio M.; Aragno, Vittoria; Testa, Valeria; Machetta, Federica; Parisi, Simone; D'Antico, Sergio; Spinetta, Roberta; Fusaro, Enrico; Grignolo, Federico M.
Abstract : Purpose. To determine the effectiveness of autologous platelet lysate (APL) eye drops in patients with primary Sjögren syndrome (SS) dry eye, refractory to standard therapy, in comparison with patients treated with artificial tears. We focused on the effect of APL on cornea morphology with the in vivo confocal microscopy (IVCM). Methods. Patients were assigned to two groups: group A used autologous platelet lysate QID, and group B used preservative-free artificial tears QID, for 90 days. Ophthalmological assessments included ocular surface disease index (OSDI), best corrected visual acuity (BCVA), Schirmer test, fluorescein score, and breakup time (BUT). A subgroup of patients in group A underwent IVCM: corneal basal epithelium, subbasal nerves, Langerhans cells, anterior stroma activated keratocytes, and reflectivity were evaluated. Results. 60 eyes of 30 patients were enrolled; in group A (n = 20 patients) mean OSDI, fluorescein score, and BUT showed significant improvement compared with group B (n = 10 patients). The IVCM showed a significant increase in basal epithelium cells density and subbasal nerve plexus density and number and a decrease in Langerhans cells density (p < 0.05 ). Conclusion. APL was found effective in the treatment of SS dry eye. IVCM seems to be a useful tool to visualize cornea morphologic modifications.